Transcriptional activation of human GM3 synthase (hST3Gal V) gene by valproic acid in ARPE-19 human retinal pigment epithelial cells - Song, N.R., Dong-A University, Busan, Republic of Korea; Kim, S.J., Dong-A University, Busan, Republic of Korea; Kwon, H.Y., Dong-A University, Busan, Republic of Korea; Son, S.W., Dong-A University, Busan, Republic of Korea; Kim, K.S., Dong-A University, Busan, Republic of Korea; Ahn, H.B., Dong-A University, Busan, Republic of Korea; Lee, Y.C., Dong-A University, Busan, Republic of Korea (BMB reports, 2011)
The present study demonstrated that valproic acid (VPA) transcriptionally regulates human GM3 synthase (hST3Gal V), which catalyzes ganglioside GM3 biosynthesis in ARPE-19 human retinal pigment epithelial cells. For this, we characterized the promoter region of the hST3Gal V gene. Functional analysis of the 5'-flanking region of the hST3Gal V gene revealed that the -177 to -83 region functions as the VPA-inducible promoter and that the CREB/ATF binding site at -143 is crucial for VPA-induced expression of hST3Gal V in ARPE-19 cells. In addition, the transcriptional activity of hST3Gal V induced by VPA in ARPE-19 cells was inhibited by SP600125, a c-Jun N-terminal kinase (JNK) inhibitor. In summary, our results identified the core promoter region in the hST3Gal V promoter and for the first time demonstrated that ATF2 binding to the CREB/ATF binding site at -143 is essential for transcriptional activation of hST3Gal V in VPA-induced ARPE-19 cells.